TRANSFORMASI SISTEM KEAMANAN DATA MELALUI BIOMETRIK DI INDONESIA PERSPEKTIF TEKNOLOGI HUKUM - Anjar Setiarma; Elfrida Ratnawati Gultom (Ensiklopedia of Journal, 2023)
Technological advances have driven the growth of e-commerce in Indonesia, which has had an impact on the development of data security systems in the e-commerce sector, such as biometric technology which is the most practical mechanism for identifying and authenticating human individuals in a reliable and fast way through the unique characteristics of each individuals and has been used in many applications to identify humans using fingerprints, faces, iris patterns, facsimile signatures, facsimile signatures, fac Cases of crimes against personal data are still rife in Indonesia, indicating weaknesses in the country's data security framework. The study methodology employed is normative legal research utilizing secondary data, followed by an analytical approach and a deductive approach to legislation. The results of this study indicate that by type of biometric data can be divided into three types namely physical, physical, and behavioral. Legal technology that can be utilized in data security systems such as online dispute resolution features, board governance, cybersecurity, and data privacy compliance. In establishing the legal system, it is hoped that the government will not only focus on legal substance and legal structure, the government must elaborate on the legal culture by utilizing national biometric technology and legal technology in the data security system, thus the effectiveness and standardization of national personal data protection can be realized immediately.